A clicking larynx: Diagnostic and therapeutic challenges. (26th September 2017) - Heuveling, Derrek A.; van Loon, Maarten C.; Rinkel, Rico N. P. M.
Abstract : A clicking larynx can be described as a clicking sensation in the neck on swallowing or when moving the head, often associated with a tender or painful area in the neck. Diagnosis and therapy are challenging. In this article, we present a case report and overview of the current literature. The clicking larynx most often is reported to be a result of a displaced cornu superior of the thyroid cartilage, an enlarged greater cornu of the hyoid bone, or a short distance between the thyroid cartilage and hyoid bone. If a possible cause is identified, surgery can be offered to the patient, although an explanation of the possible underlying anatomical cause also could be satisfying for the patient and avert surgery. Laryngoscope, 128:697–700, 2018